Alginate and HM-pectin in sports-drink give rise to intra-gastric gelation in vivo. Issue 12 (3rd December 2019) - Marciani, Luca; Lopez-Sanchez, Patricia; Pettersson, Stefan; Hoad, Caroline; Abrehart, Nichola; Ahnoff, Martin; Ström, Anna
Abstract : A polysaccharide drink containing 14% maltodextrin/fructose shows in vivo gelling behaviour as evidenced by magnetic resonance imaging. Abstract : The addition of gelling polysaccharides to sport-drinks may provide improved tolerability of drinks with high concentration of digestible carbohydrates (CHO), otherwise known to increase the risk of gastro-intestinal complaints among athletes under prolonged exercise. The physico-chemical properties of a drink containing 14 wt% of digestible CHO (0.7 : 1 fructose and maltodextrin-ratio), 0.2 wt% of HM-pectin/alginate and 0.06 wt%. sodium chloride were examined under in vitro gastric conditions using rheology and large deformation testing. The in vivo gelling behaviour of the drink was studied using magnetic resonance imaging of subjects at rest together with blood glucose measurements. The in vivo results confirm gelation of the test drink, with no gel remaining in the stomach at 60 min and blood glucose values were similar to control. The physico-chemical characterisation of the acidified test drink confirms the formation of a weak gel through which low M w CHO can diffuse.